hCG production by mucinous adenocarcinoma of the ovary in a reproductive aged woman - Vincent Wagner; Heather Winn; Andreea Newtson; David Bender; Megan McDonald (Elsevier, 2018)
When elevated serum hCG is discovered during the work up of a gynecologic tumor, it is paramount to identify the source of hCG prior to initiation of treatment. Potential sources of hCG include viable intrauterine pregnancy, ectopic pregnancy, miscarriage, gestational trophoblastic disease, pituitary hCG production, phantom hCG (heterophilic antibody interference), and tumor production. Here, we present a case of elevated hCG in a young women with a large complex pelvic mass. Prior to treatment initiation, the patient underwent work up for hCG elevation, which was ultimately found to be from tumor production. Pathologic examination revealed the mass to be a mucinous adenocarcinoma of the ovary with aberrant expression of hCG, rather than the more typical hCG producing germ cell tumor. We detail the preoperative evaluation process of hCG elevation. Additionally, we discuss the role of hCG in ovarian cancer and influence on tumorigenesis and management. Keywords: hCG, Epithelial ovarian cancer, Mucinous ovarian adenocarcinoma